Ta3N5-based photoelectrode based on vapor deposition technology and preparation method thereof

The preparation of Ta3N5-based photoelectrode with multi-layer film structure through vapor deposition technology solves the problem of low performance of existing Ta3N5 photoelectrodes, realizes efficient photoelectric utilization and full spectrum utilization, and significantly improves PEC conversion efficiency.

CN120210810APending Publication Date: 2025-06-27ZHEJIANG UNIV

Patent Information

Application Number
CN202510192560.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The performance of existing Ta3N5 photoelectrodes in PEC water decomposition is lower than theoretically expected, mainly due to its high intrinsic charge recombination rate, poor surfactant sites and poor stability, and its inability to effectively utilize the full spectrum, resulting in low PEC conversion efficiency.

Method used

The Ta3N5-based photoelectrode with a multi-layer film structure is prepared using vapor deposition technology, including magnetron sputtering, electron beam evaporation and thermal nitriding treatment. This structure consists of Ti, Pt, TixAly, Ta3N5, NiFeCoOz and MNPs nanometallic particles. The photoelectric performance is improved through the TixAly alloy layer and the NiFeCoOz cocatalyst layer, and photothermal-photoelectric coupling is achieved through the LSPR effect of MNPs.

Benefits of technology

It significantly improves the photoelectric utilization efficiency and stability of Ta3N5 photoelectrode, reduces the amount of precious metals, expands the application range, and realizes the full spectrum utilization, and improves the PEC conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120210810A_ABST
    Figure CN120210810A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photoelectrocatalysis, and aims to provide a Ta3N5-based photoelectrode based on a vapor deposition technology and a preparation method of the Ta3N5-based photoelectrode. According to the photoelectrode, quartz glass serves as a substrate, and the substrate is provided with a multi-layer film structure which is formed on the basis of magnetron sputtering, electron beam evaporation, thermal nitriding treatment, electrochemical deposition and coating; the multilayer film structure sequentially comprises a first Ti metal layer, a Pt conductive metal layer, a Ti < x > Al < y > alloy layer, a Ta3N5 layer, a NiFeCoOz cocatalyst layer and MNPs nano metal particles from bottom to top. The use amount of precious metal can be greatly saved, the preparation cost is reduced, and the application range is expanded; the mobility of photoelectrons can be improved, the transport of photon-generated carriers can be improved, and the photoelectric utilization efficiency can be greatly improved; and the energy loss between two photo-thermal application interfaces is greatly reduced, so that the photo-thermal utilization efficiency of the single photoelectrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photoelectrocatalysis, and particularly to a Ta3N5-based photoanode based on vapor deposition technology and a preparation method thereof. Background Art

[0002] Solar energy is considered to be a highly promising energy source due to its wide availability and clean application environment. Developing devices and systems for converting solar energy into sustainable energy is one of the ideal solutions to meet the growing global energy demand and address environmental problems related to fossil fuel consumption.

[0003] Photoelectrochemical (PEC) water splitting for hydrogen production is considered a promising method for converting solar energy into renewable clean hydrogen fuel, and semiconductor materials that absorb sunlight and generate electron-hole pairs are the core of this method. However, the PEC conversion efficiency is severely limited by the efficiency of the oxygen evolution reaction (OER) on the semiconductor anode. Therefore, designing and preparing efficient anode materials is crucial for future solar energy utilization. Among various semiconductor materials, tantalum nitride (Ta3N5) is widely regarded as an attractive photoanode material due to its suitable sunlight absorption bandgap (2.0 - 2.1 eV) and relatively high theoretical maximum solar conversion efficiency (15.9%). However, the reported performance of Ta3N5 photoanodes in PEC water splitting is usually far lower than the theoretical expectation, mainly due to its high intrinsic charge recombination rate, poor surface active sites, and poor stability. In recent years, many modification methods for photoelectrochemical anode catalysts have been widely reported, including element doping, heterostructure construction, and cocatalyst modification, etc., aiming to enhance the PEC water oxidation activity of the Ta3N5 anode, and some important progress has been made in the past decade. However, despite these improvements, the Ta3N5 anode is still limited by its inherent bulk defects and rapid carrier recombination, resulting in a high onset potential and poor PEC conversion efficiency. In addition, the Ta3N5 anodes in the existing literature can usually only absorb the solar spectrum of about 600 nm, causing waste of visible and infrared light and limiting the effect of PEC applications.

[0004] Photothermal catalysis (PTC) has attracted much attention because it can improve the catalytic efficiency by reacting in a wider range of light wavelengths. Through the local surface plasmon resonance (LSPR) effect, metal nanoparticles can strongly absorb the solar spectrum including visible light and near-infrared light, and effectively convert light energy into chemical energy through thermal and electronic effects. Therefore, the coupling of photothermal catalysis and photoelectrocatalysis is expected to improve the catalytic activity and achieve full-spectrum utilization, becoming the focus of research. However, current research mainly focuses on the way of combining two electrode modules. For example, in the Chinese invention patent "Method for preparing hydrocarbons by photoelectric-photothermal coupling with water and CO2 as raw materials" (CN116770331A), by integrating a photoelectrocatalytic sub-module and a photothermal catalytic sub-module into the same transparent reactor, the hierarchical and quality-separated full-spectrum utilization of the solar spectrum is realized by combining solar photoelectrocatalysis and photothermal catalysis technologies. However, this separated use method can only exert their respective catalytic performances respectively. Although they can complement each other, it is difficult to achieve the mutual promotion of the two.

[0005] The applicant proposed in the invention patent application "Ta3N5-based photoanode based on magnetron sputtering" (CN119040940A) that this Ta3N5-based photoanode uses quartz glass as the substrate, and has a multi-layer film structure formed on the substrate based on magnetron sputtering and after thermal nitridation and coating treatments. Since the photothermal-photoelectric coupling is realized on a single photoanode product, the energy loss between the two photothermal application interfaces can be greatly reduced, thereby improving the photothermal utilization efficiency of the single photoanode. However, there are still deficiencies in the preparation process and the design of the multi-layer film structure of this technology. For example: the deposition rate of the magnetron sputtering process is low, and it is difficult to control the film quality and uniformity, resulting in more defects inside the semiconductor; the deposited Ti x Si y layer is a nano-level composite layer with poor conductivity, and large energy losses occur during the electron transmission process.

[0006] Therefore, it is necessary to propose further technical solutions to solve the above problems. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a Ta3N5-based photoanode based on vapor deposition technology and its preparation method. This method uses vapor deposition technologies including electron beam evaporation and magnetron sputtering to bond the Ta3N5 layer on the Pt / Ti layer with a Ti x Al y film layer, which can promote the separation and transmission of photo-generated carriers.

[0008] To solve the above technical problems, the solution of the present invention is:

[0009] Provided is a Ta3N5-based photoanode based on vapor deposition technology. The Ta3N5-based photoanode uses quartz glass as a substrate, and has a multi-layer film structure formed on the substrate after magnetron sputtering, electron beam evaporation, thermal nitridation treatment, electrochemical deposition, and coating; the multi-layer film structure sequentially includes a first Ti metal layer, a Pt conductive metal layer, a Ti x Al y alloy layer, a Ta3N5 layer, a NiFeCoO z co-catalyst layer, and MNPs nano metal particles; the Ti x Al y alloy layer is a homogeneous material layer formed by the reaction and combination transformation of a second Ti metal layer and an Al2O3 layer, and the Ta3N5 layer is a homogeneous material layer formed by the reaction and combination transformation of a Ta2O5 layer and NH3; the NiFeCoO z co-catalyst layer is a homogeneous material layer formed by applying gradient bias deposition; the MNPs metal particles contain Au or Pt, and M refers to Au or Pt with photothermal properties.

[0010] As a preferred embodiment of the present invention, the thickness range of the first Ti metal layer is 2-50 nm, the thickness range of the Pt conductive metal layer is 100-200 nm, and the Ti x Al y layer has a thickness range of 20-100 nm, and the Ta3N5 layer has a thickness range of 500-700 nm; the NiFeCoO z co-catalyst layer has a thickness range of 2-10 nm; the average particle size of the MNPs nano metal particles is 5-20 nm.

[0011] As a preferred embodiment of the present invention, the thickness ratio of the second Ti metal layer to the Al2O3 layer is x / y, and its value range is 1-5; the value range of z in the NiFeCoO z co-catalyst layer is 2-4.

[0012] The present invention further provides a preparation method for the aforementioned Ta3N5-based photoanode based on vapor deposition technology, including the following steps:

[0013] (1) Use a quartz glass plate of appropriate size as a substrate, and clean it successively with acetone, absolute ethanol, dilute sulfuric acid, and deionized water;

[0014] (2) First, use the magnetron sputtering process to sequentially deposit a first Ti metal layer and a Pt conductive metal layer on the substrate; according to the design scheme of the photoanode, after locally shielding the reserved area for conduction, continue to use the magnetron sputtering process to sequentially deposit a second Ti metal layer and an Al2O3 layer, and finally use the electron beam evaporation process to deposit a Ta2O5 layer;

[0015] (3) Transfer the sample that has completed the multi-layer deposition process into a horizontal quartz tube furnace for thermal nitridation treatment; during this process, the two materials of the second Ti metal layer and the Al2O3 layer react and combine to transform into a uniform Ti x Al y alloy layer, and the Ta2O5 layer combines with NH3 to transform into a uniform Ta3N5 layer;

[0016] (4) Continue to deposit the co-catalyst layer NiFeCoO on the surface of Ta3N5 using the electrochemical deposition technique z , apply a gradient bias during the electrodeposition process, and rinse with deionized water after deposition;

[0017] (5) Prepare metal nanoparticles (MNPs) using the liquid-phase reduction method. After centrifuging, dispersing, and diluting the obtained MNPs colloid, spin-coat it on the Ta3N5 layer on the surface of the sample; further perform a drying treatment at room temperature to obtain a Ta3N5-based photoanode with MNPs metal particles on the surface, denoted as MNPs@NiFeCoO z / Ta3N5 / Ti x Al y photoanode.

[0018] As a preferred embodiment of the present invention, during the magnetron sputtering treatment and electron beam evaporation process in step (2), the deposition thicknesses of each layer on the sample are as follows: the first Ti metal layer is 2 - 50 nm, the Pt metal conductive layer is 100 - 200 nm; the second Ti metal layer is 2 - 50 nm, the Al2O3 layer is 20 - 100 nm, and the Ta2O5 layer is 500 - 700 nm.

[0019] As a preferred embodiment of the present invention, in step (2): during the magnetron sputtering treatment, introduce Ar gas into the magnetron sputtering chamber at a rate of 37 sccm and maintain the lowest vacuum degree at 6.7E -7 MPa; during the electron beam evaporation process, introduce Ar gas into the deposition chamber at a rate of 30 sccm to keep the chamber pressure at 1.0E -4 Torr, and deposit at a deposition rate.

[0020] As a preferred embodiment of the present invention, during the thermal nitridation treatment process in step (3), heat the sample from room temperature to 950 - 1000 °C at a rate of 5 °C / min under normal pressure, keep it for 6 h, and then cool it naturally to room temperature; during this process, introduce flowing ammonia gas to maintain the ammonia atmosphere in the treatment chamber.

[0021] As a preferred embodiment of the present invention, step (4) specifically includes:

[0022] Take Fe(NO3)3·9H2O, Ni(NO3)2·6H2O and Co(NO3)2·6H2O in a molar ratio of 1:3:2, add them to an appropriate amount of deionized water, and after mixing evenly, prepare an electrolyte solution for electrochemical deposition; immerse the sample after thermal nitridation treatment in the electrolyte solution as the working electrode, use a calomel electrode as the reference electrode and a platinum sheet as the counter electrode, and carry out the electrochemical deposition process using a three-electrode system; during the electrochemical deposition process, maintain continuous stirring at 400 rpm, and at the same time apply a gradient bias of 0.65 - 0.9 V, and the deposition time is 60 s.

[0023] As a preferred embodiment of the present invention, in the step (5), the chloro complex acid of Au or Pt is fully oscillated to obtain an MNPs precursor solution, and further reacted fully with potassium carbonate and ascorbic acid, then hydroxylamine hydrochloride is added, and shaken until the color is uniform; deionized water is added to the reaction product for centrifugation to obtain MNPs colloid; anhydrous ethanol is added for ultrasonic dispersion, and the dispersed suspension is diluted at a ratio of 1:50 for spin coating operation, and the coating amount is 100 - 400 μL / cm 2 。

[0024] As a preferred embodiment of the present invention, in the step (5), by controlling the reaction time, cleaning operation and coating thickness of the MNPs precursor solution, the average particle size of the MNPs nanometal particles on the surface of the Ta3N5-based photoanode is 5 - 20 nm and can absorb specific wavelengths in the wavelength range of 500 - 620 nm.

[0025] Description of the invention principle:

[0026] In the existing PEC technology, tantalum nitride (Ta3N5) as the anode usually needs to be carried on noble metals (such as Pt), resulting in too high cost to be popularized and applied. In addition, how to couple the Ta3N5 anode with the PTC technology is also one of the difficult problems.

[0027] The present invention innovatively proposes to combine magnetron sputtering, electron beam evaporation and thermal nitridation technologies; realizes the conversion of the Ti-Al2O3 layer combination into a Ti x Al y layer, and the combination of Ta2O5-NH3 is converted into a Ta3N5 layer; Ti x Al y is an alloy layer, which acts as a binder to ensure the tight combination of Ta3N5 and noble metals such as Pt, greatly saving the consumption of noble metals and creating conditions for expanding the application range. In addition, Ti x Al y The alloy layer can, on the one hand, improve the mobility of photoelectrons and induce the separation and migration of electron-hole pairs (EHPs); on the other hand, Ti x Aly The Fermi levels of Ta3N5 are at -4.13 eV and -4.1 eV respectively, and their energy levels are matched, which is beneficial to improving the transport of photo-generated carriers.

[0028] The present invention further innovatively proposes that by using the MNPs precursor solution prepared by the liquid-phase reduction method, metal nanoparticles that absorb specific wavelength bands can be obtained by controlling the cleaning step and reaction time. By coating it on the surface of the Ta3N5 film layer to form a load of metals (such as Au, Pt, etc.) with photothermal properties, the photothermal-photoelectric coupling on a single photo-electrode product is realized. Therefore, the product further reduces the manufacturing cost, improves the photothermal utilization efficiency, and can expand the application range.

[0029] Compared with the applicant's previous research results (CN119040940A), the present invention uses a more refined electron beam evaporation process to deposit the Ta2O5 layer, obtaining a high-purity, dense and uniform thin film with reduced internal defects; compared with the Ti x Si y nanoscale composite layer, the present invention uses a Ti x Al y alloy layer, which has better conductivity, and a higher Fermi level is beneficial to reducing the energy loss of electrons during transmission, and the quantum efficiency is improved.

[0030] Compared with the prior art, the beneficial effects of the present invention are:

[0031] 1. Compared with the traditional method of loading Ta3N5 on a metal substrate, the present invention uses a specific Ta3N5 / Ti x Al y generation method to bond the multi-layer film structure to the quartz glass substrate, which can greatly save the amount of precious metals, reduce the preparation cost, and expand the application range.

[0032] 2. In the multi-layer film structure of the product of the present invention, since Ti x Al y is an alloy layer, it can improve the mobility of photo-electrons, utilize ultraviolet-visible light to enhance the separation and migration of photo-induced EHPs, and the Fermi levels of Ti x Al y and Ta3N5 are matched, which is beneficial to improving the transport of photo-generated carriers; therefore, the photoelectric utilization efficiency can be greatly improved.

[0033] 3. The product of the present invention uses a multi-layer film structure to coat the surface of the Ta3N5 film layer with nano-metal particles of Au, Pt with photothermal properties, abandoning the separate use method in the traditional technology, greatly reducing the energy loss between the two photothermal application interfaces, thereby improving the photothermal utilization efficiency of the single photo-electrode.

[0034] 4. Compared with the applicant's previous research results (CN119040940A), the present invention further solves the deficiencies existing in the magnetron sputtering process and the Ti x Si y nanoscale composite layer. By adopting a more refined electron beam evaporation process, a high-purity, dense and uniform thin film is obtained, and a Ti x Al y alloy layer with better conductivity and higher Fermi level is designed to achieve an improvement in quantum efficiency, thereby significantly enhancing the performance of the photoanode. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a schematic diagram of the structure and manufacturing process of MNPs@NiFeCoO z / Ta3N5 / Ti x Al y in the present invention.

[0036] Figure 2 are HRTEM images of MNPs@NiFeCoO z / Ta3N5 / Ti x Al y at different magnifications.

[0037] Figure 3 is a comparison chart of the photocurrent density and onset potential between the photoanode prepared by the present invention and the photoanode of the prior art.

[0038] Figure 4 is a comparison chart of the incident monochromatic light - electron conversion efficiency (IPCE) between the photoanode prepared by the present invention and the photoanode in the applicant's previous research results (CN119040940A).

[0039] Figure 5 is a comparison chart of the applied bias photo - electricity conversion efficiency (ABPE) and onset potential between the photoanode prepared by the present invention and the photoanode in the applicant's previous research results (CN119040940A). DETAILED DESCRIPTION OF THE INVENTION

[0040] The present invention will be further described in detail below in conjunction with the specific embodiments:

[0041] In the present invention, magnetron sputtering, electron beam evaporation and thermal nitridation treatment technologies are all mature processes for semiconductor device processing. The preparation of NiFeCoO z cocatalyst and metal nanoparticle (MNPs) precursor solution is also recorded in many public literatures. The present invention does not make special requirements, so it will not be elaborated here.

[0042] The first part: Implementation method of the present invention

[0043] 1. Preparation method of Ta3N5-based photoanode

[0044] (1) Use a quartz glass plate with appropriate size (such as 10×15×1 mm 3 ) as the substrate, and clean it successively with acetone, absolute ethanol, dilute sulfuric acid and deionized water;

[0045] (2) First, deposit the first Ti metal layer and Pt conductive metal layer on the substrate by magnetron sputtering process; according to the design scheme of the photoanode, perform local masking treatment on the reserved area for conduction; first deposit the second Ti metal layer and Al2O3 layer by magnetron sputtering process successively. During the process, introduce Ar gas into the magnetron sputtering chamber at a rate of 37 sccm, and maintain the minimum vacuum degree at 6.7E -7 MPa; then deposit the Ta2O5 layer by electron beam evaporation process. During the process, introduce Ar gas into the deposition chamber at a rate of 30 sccm to keep the chamber pressure at 1.0E -4 Torr, and deposit at a deposition rate.

[0046] After the above treatment, the deposition thicknesses of each layer on the sample are as follows: the first Ti metal layer is 2 - 50 nm, the Pt metal conductive layer is 100 - 200 nm; the second Ti metal layer is 2 - 50 nm, the Al2O3 layer is 20 - 100 nm, and the Ta2O5 layer is 500 - 700 nm.

[0047] (3) Transfer the sample that has completed the multi-layer deposition treatment into a horizontal quartz tube furnace, and perform: heat the sample from room temperature to 950 - 1000 °C at a rate of 5 °C / min under normal pressure, keep it for 6 h and then cool it naturally to room temperature. Introduce flowing ammonia gas during this process to maintain the ammonia atmosphere in the treatment chamber.

[0048] After the thermal nitridation treatment, the two materials of the second Ti metal layer and the Al2O3 layer react and combine to transform into a uniform Ti x Al y alloy layer, and the Ta2O5 layer combines with NH3 to transform into a uniform Ta3N5 layer;

[0049] (4) Take Fe(NO3)3·9H2O, Ni(NO3)2·6H2O and Co(NO3)2·6H2O in a molar ratio of 1:3:2, add them to an appropriate amount of deionized water, and mix evenly to prepare an electrolyte solution for electrochemical deposition.

[0050] Immerse the sample after thermal nitridation treatment in the electrolyte solution as the working electrode, use the calomel electrode as the reference electrode and the platinum sheet as the counter electrode, and continue to deposit the cocatalyst layer NiFeCoO on the Ta3N5 surface by using the three-electrode system z; Maintain continuous stirring at 400 rpm while applying a gradient bias of 0.65 - 0.9 V for a deposition time of 60 s to form NiFeCoO z The thickness range of the co - catalyst layer is 2 - 10 nm, where the value of z ranges from 2 - 4, which is related to the magnitude of the applied gradient bias. After this process is completed, the sample needs to be thoroughly rinsed with deionized water.

[0051] (5) Prepare a metal nanoparticle (MNPs) colloid using the liquid - phase reduction method. After centrifugation, dispersion, and dilution, it is coated on the Ta3N5 layer on the surface of the sample, and after drying treatment, MNPs metal particles are formed on the surface layer.

[0052] The preparation of metal nanoparticles (MNPs) can use existing publicly available technologies. The following is an example of the scheme: First, add 4.5 mL of ultrapure water and 100 μL of a 24 mmol / L precious metal (Au or Pt) chloro - complex acid to a clean container. After sufficient oscillation, an MNPs precursor solution is obtained. Then, continue to add 100 μL of a 0.2 mol / L potassium carbonate and 100 μL of a 1 mmol / L ascorbic acid, and react fully for 20 minutes. After the reaction ends, quickly add 200 μL of a 10 mmol / L hydroxylamine hydrochloride, and shake well until the color is uniform; centrifuge at 11000 rmp for 5 - 20 min, discard the supernatant, add deionized water to the volume before centrifugation, perform centrifugation under the same conditions, and aspirate the supernatant to obtain MNPs colloid; add anhydrous ethanol to the volume before centrifugation, and perform ultrasonic treatment to disperse it to ensure uniformity.

[0053] Dilute the dispersed suspension with deionized water at a ratio of 1:50, and then spin - coat it on the Ta3N5 layer on the surface of the photoanode, with a coating amount of 100 - 400 μL / cm 2 . Conduct drying treatment at room temperature to obtain a Ta3N5 - based photoanode with MNPs metal particles on the surface layer, denoted as MNPs@NiFeCoO z / Ta3N5 / Ti x Al y photoanode.

[0054] By controlling the reaction time, cleaning operation, and coating thickness of the MNPs precursor solution, the average particle size of the MNPs nano - metal particles on the surface of the Ta3N5 - based photoanode is 5 - 20 nm, and it can absorb specific wavelengths in the wavelength range of 500 - 620 nm. The larger the particle size of the MNPs nano - metal particles, the red - shift of the absorbed wavelength will occur, moving towards the direction of increasing wavelength.

[0055] 2. Product characteristics of the Ta3N5 - based photoanode

[0056] Ta3N5-based photoanode products prepared by the above method: using quartz glass as the substrate, having a multi-layer film structure formed on the substrate based on magnetron sputtering, electron beam evaporation, followed by thermal nitridation treatment, electrochemical deposition, and coating; the multi-layer film structure sequentially includes a first Ti metal layer, a Pt conductive metal layer, a Ti x Al y alloy layer, a Ta3N5 layer, a NiFeCoO z cocatalyst layer, and MNPs nano metal particles; the Ti x Al y alloy layer is a homogeneous material layer formed by the reaction and combination transformation of the second Ti metal layer and the Al2O3 layer, and the Ta3N5 layer is a homogeneous material layer formed by the reaction and combination transformation of the Ta2O5 layer and NH3; the NiFeCoO z cocatalyst layer is a homogeneous material layer formed by applying gradient bias deposition; the MNPs metal particles contain Au or Pt, and M represents Au or Pt with photothermal properties.

[0057] As an optional example, the thickness range of the first Ti metal layer is 2 - 50 nm, the thickness range of the Pt conductive metal layer is 100 - 200 nm, the thickness range of the Ti x Al y layer is 20 - 100 nm, the thickness range of the Ta3N5 layer is 500 - 700 nm, and the thickness range of the NiFeCoO z cocatalyst layer is 2 - 10 nm. The average particle size of the MNPs nano metal particles is 5 - 20 nm.

[0058] 3. Example of the usage method of Ta3N5-based photoanode products

[0059] An example of the usage method of the photoanode products prepared in the present invention is as follows: Use a Nafion 117 membrane to separate the Pt cathode chamber and the photoanode chamber. Use the photoanode as the working electrode, a platinum sheet as the counter electrode, and select a calomel reference electrode, and connect to an electrochemical workstation.

[0060] In the embodiments of the present invention, simulate standard sunlight through an AM 1.5G filter, and calibrate the intensity to 100 mW·cm -2 , and perform photoelectrochemical measurement on the photoanode products under simulated sunlight.

[0061] The second part: Examples and comparative examples

[0062] Example 1

[0063] According to the alloy layer general formula Ti x Al y (where x / y = 1) and the cocatalyst layer general formula NiFeCoOz (where z = 2), prepare PtNPs@NiFeCoO2 / Ta3N5 / Ti x Al y 。

[0064] Use a quartz glass with dimensions of 10×15×1 mm 3 as the substrate, and clean it successively with acetone, absolute ethanol, dilute sulfuric acid, and deionized water. Deposit a 2-nm-thick Ti layer on the quartz substrate by sputtering, and then deposit a 100-nm-thick Pt layer. Partially mask the sample so that the exposed area is 10×10 mm 2 , and then successively deposit a 2-nm-thick Ti layer and a 20-nm-thick Al2O3 layer by sputtering. During the magnetron sputtering process, introduce Ar gas into the chamber at a rate of 37 sccm, and maintain the minimum vacuum degree at 5.0E -6 Torr (i.e., 6.7E -7 MPa). Use the electron beam evaporation method to deposit a 500-nm-thick Ta2O5 layer on the photoanode at a deposition rate of . During the electron beam evaporation process, introduce Ar gas into the deposition chamber at a rate of 30 sccm to keep the chamber pressure at 1.0E -4 Torr. By thermally nitriding the Ta2O5 / Al2O3 / Ti / Pt / Ti film in a horizontal quartz tube furnace, heat it from room temperature to 950 °C at a rate of 5 °C / min under ambient pressure, hold for 6 h, and then cool it naturally to room temperature to obtain Ta3N5 / Ti x Al y film. During this process, introduce flowing ammonia gas to maintain the ammonia atmosphere in the processing chamber.

[0065] Use the electrochemical deposition technique to deposit the cocatalyst layer NiFeCoO2 on the surface of Ta3N5. Specifically, the volume of the electrolyte solution is 200 mL, which is composed of 20 mM Fe(NO3)3·9H2O, 60 mM Ni(NO3)2·6H2O, 40 mM Co(NO3)2·6H2O, and deionized water. Stir it at 800 rpm for 30 min to ensure uniform mixing. During the electrodeposition process, maintain continuous stirring at 400 rpm, and at the same time apply a bias of 0.65 V for a deposition time of 60 s. After this process is completed, the sample needs to be thoroughly rinsed with deionized water.

[0066] Prepare a precursor solution containing 4.5 mL of ultrapure water, 100 μL of 24 mmol / L chloroauric acid, 100 μL of 0.2 mol / L potassium carbonate, and 100 μL of 1 mol / L ascorbic acid. After reacting for 20 min, quickly add 100 μL of 10 mmol / L hydroxylamine hydrochloride and shake until the color is uniform. Take 5 mL of the solution, centrifuge at 11000 rpm for 5 min. After obtaining the AuNPs colloid, discard the supernatant. Then add deionized water to 5 mL, centrifuge under the same conditions, discard the supernatant, add absolute ethanol to 5 mL, and ultrasonically treat until dispersed to ensure uniformity. Finally, take 1 mL of the solution and dilute it 50 times with deionized water. Spin-coat 100 μL / cm 2 onto the surface of the photoanode to obtain AuNPs@NiFeCoO2 / Ta3N5 / Ti x Al y photoelectrode.

[0067] The multilayer film structure of the Ta3N5-based photoelectrode sequentially includes a first Ti metal layer, a Pt conductive metal layer, a Ti x Al y alloy layer, a Ta3N5 layer, and a NiFeCoO2 cocatalyst layer. The thicknesses of each layer are: 2 nm, 100 nm, 20 nm, 500 nm, 2 nm; the average particle size of the MNPs nanometal particles is 5 nm, which can absorb specific wavelengths in the wavelength range of 500 - 530 nm.

[0068] Example 2

[0069] According to the alloy layer general formula Ti x Al y (where x / y = 2) and the cocatalyst layer general formula NiFeCoO z (where z = 3), prepare PtNPs@NiFeCoO3 / Ta3N5 / Ti x Al y .

[0070] Use a quartz glass with dimensions of 10×15×1 mm 3 as the substrate, and clean it successively with acetone, absolute ethanol, dilute sulfuric acid, and deionized water. Deposit a 50-nm-thick Ti layer on the quartz substrate by sputtering, and then deposit a 100-nm-thick Pt layer. Partially mask the sample so that the exposed area is 10×10 mm 2 , and then successively deposit a 50-nm-thick Ti layer and a 50-nm-thick Al2O3 layer by sputtering. During the magnetron sputtering process, introduce Ar gas into the chamber at a rate of 37 sccm and maintain the minimum vacuum degree at 5.0E -6 Torr. Use the electron beam evaporation method to Deposit a Ta2O5 layer with a thickness of 650 nm on the photoanode at a deposition rate. During the electron beam evaporation process, introduce Ar gas into the deposition chamber at a rate of 30 sccm to keep the chamber pressure at 1.0E -4 Torr. By thermally nitriding the Ta2O5 / Al2O3 / Ti / Pt / Ti thin film in a horizontal quartz tube furnace, heat it from room temperature to 970 °C at a rate of 5 °C / min under ambient pressure, hold for 6 h, and then cool it naturally to room temperature to obtain Ta3N5 / Ti x Al y thin film. During this process, introduce flowing ammonia gas to maintain the ammonia atmosphere in the processing chamber.

[0071] Use electrochemical deposition technology to deposit a co-catalyst layer NiFeCoO3 on the surface of Ta3N5, specifically including: the volume of the electrolyte solution is 200 mL, which is composed of 20 mM Fe(NO3)3·9H2O, 60 mM Ni(NO3)2·6H2O, 40 mM Co(NO3)2·6H2O and deionized water, stir at 800 rpm for 30 min to ensure uniform mixing. During the electrodeposition process, maintain continuous stirring at 400 rpm, while applying a bias of 0.7 V, and the deposition time is 60 s. After this process is completed, the sample needs to be thoroughly rinsed with deionized water.

[0072] Prepare a precursor solution containing 4.5 mL of ultrapure water, 100 μL of 24 mmol / L chloroauric acid, 100 μL of 0.2 mol / L potassium carbonate, and 100 μL of 1 mol / L ascorbic acid. After reacting for 20 min, quickly add 100 μL of 10 mmol / L hydroxylamine hydrochloride and shake until the color is uniform. Take 5 mL of the solution, centrifuge at 11000 rpm for 10 min, discard the supernatant after obtaining the AuNPs colloid. Then add deionized water to 5 mL, centrifuge under the same conditions, discard the supernatant, add absolute ethanol to 5 mL, and ultrasonically treat until dispersed to ensure uniformity. Finally, take 1 mL of the solution and dilute it 50 times with deionized water, and spin-coat 200 μL / cm 2 onto the surface of the photoanode to obtain AuNPs@NiFeCoO3 / Ta3N5 / Ti x Al y photoelectrode.

[0073] The multi-layer film structure of the Ta3N5-based photoelectrode sequentially includes a first Ti metal layer, a Pt conductive metal layer, Ti x Al yAn alloy layer, a Ta3N5 layer, and a NiFeCoO3 cocatalyst layer, with the thicknesses of each layer being: 50 nm, 100 nm, 50 nm, 650 nm, 5 nm respectively; the average particle size of the MNPs nanometal particles is 10 nm, and it can absorb specific wavelengths in the wavelength range of 530 - 560 nm.

[0074] Example 3

[0075] According to the alloy layer general formula Ti x Al y , where x / y = 3; the cocatalyst layer general formula NiFeCoO z , where z = 2 to prepare PtNPs@NiFeCoO2 / Ta3N5 / Ti x Al y .

[0076] Use a quartz glass with dimensions of 10×15×1 mm 3 as the substrate, and clean it successively with acetone, absolute ethanol, dilute sulfuric acid, and deionized water. Deposit a Ti layer with a thickness of 25 nm on the quartz substrate by sputtering, and then deposit a Pt layer with a thickness of 150 nm. Partially shield the sample so that the exposed area is 10×10 mm 2 , and then successively deposit a Ti layer with a thickness of 10 nm and an Al2O3 layer with a thickness of 80 nm by sputtering. During the magnetron sputtering process, introduce Ar gas into the chamber at a rate of 37 sccm, and maintain the lowest vacuum degree at 5.0E -6 Torr. Use the electron beam evaporation method to deposit a Ta2O5 layer with a thickness of 680 nm on the photoanode at a deposition rate of . During the electron beam evaporation process, introduce Ar gas into the deposition chamber at a rate of 30 sccm to keep the chamber pressure at 1.0E -4 Torr. By thermally nitriding the Ta2O5 / Al2O3 / Ti / Pt / Ti film in a horizontal quartz tube furnace, heat it from room temperature to 980 °C at a rate of 5 °C / min under ambient pressure, hold for 6 h, and then cool it naturally to room temperature to obtain Ta3N5 / Ti x Al y film. During this process, introduce flowing ammonia gas to maintain the ammonia atmosphere in the processing chamber.

[0077] The co - catalyst layer NiFeCoO2 was deposited on the surface of Ta3N5 by electrochemical deposition technology, specifically including: the volume of the electrolyte solution was 200 mL, which was composed of 20 mM Fe(NO3)3·9H2O, 60 mM Ni(NO3)2·6H2O, 40 mM Co(NO3)2·6H2O and deionized water, and stirred at 800 rpm for 30 min to ensure uniform mixing. During the electrodeposition process, continuous stirring at 400 rpm was maintained, while a bias of 0.8 V was applied, and the deposition time was 60 s. After this process was completed, the sample needed to be thoroughly rinsed with deionized water.

[0078] Prepare a precursor solution containing 4.5 mL of ultrapure water, 100 μL of 24 mmol / L chloroplatinic acid, 100 μL of 0.2 mol / L potassium carbonate, and 100 μL of 1 mol / L ascorbic acid. After reacting for 20 min, 100 μL of 10 mmol / L hydroxylamine hydrochloride was quickly added and shaken until the color was uniform. Take 5 mL of the solution, centrifuge at 11000 rpm for 15 min. After obtaining the PtNPs colloid, discard the supernatant. Then add deionized water to 5 mL, centrifuge under the same conditions, discard the supernatant, add absolute ethanol to 5 mL, and ultrasonically treat until dispersed to ensure uniformity. Finally, take 1 mL of the solution and dilute it 50 times with deionized water, and spin - coat 300 μL / cm 2 onto the surface of the photoanode to obtain PtNPs@NiFeCoO2 / Ta3N5 / Ti x Al y photoelectrode.

[0079] The multi - layer film structure of the Ta3N5 - based photoelectrode sequentially includes a first Ti metal layer, a Pt conductive metal layer, a Ti x Al y alloy layer, a Ta3N5 layer, and a NiFeCoO2 co - catalyst layer from bottom to top. The thicknesses of each layer are: 25 nm, 150 nm, 80 nm, 680 nm, 8 nm; the average particle size of the MNPs nano - metal particles is 15 nm, which can absorb specific wavelengths in the wavelength range of 560 - 590 nm.

[0080] Example 4

[0081] According to the alloy layer general formula Ti x Al y (where x / y = 5) and the co - catalyst layer general formula NiFeCoO z (where z = 4), prepare PtNPs@NiFeCoO4 / Ta3N5 / Ti x Al y .

[0082] Adopt a size of 10×15×1 mm 3Using quartz glass as the substrate, it was successively cleaned with acetone, absolute ethanol, dilute sulfuric acid and deionized water. A Ti layer with a thickness of 30 nm was deposited on the quartz substrate by sputtering, and then a Pt layer with a thickness of 200 nm was deposited. Part of the sample was masked so that the exposed area was 10×10 mm 2 , and then a Ti layer with a thickness of 50 nm and an Al2O3 layer with a thickness of 100 nm were successively deposited by sputtering. During the magnetron sputtering process, Ar gas was introduced into the chamber at a rate of 37 sccm, and the minimum vacuum was maintained at 5.0E -6 Torr. The method of electron beam evaporation was used to deposit a Ta2O5 layer with a thickness of 700 nm on the photoanode at a deposition rate of / s. During the electron beam evaporation process, Ar gas was introduced into the deposition chamber at a rate of 30 sccm to keep the chamber pressure at 1.0E -4 Torr. By thermally nitriding the Ta2O5 / Al2O3 / Ti / Pt / Ti thin film in a horizontal quartz tube furnace, it was heated from room temperature to 1000 °C at a rate of 5 °C / min under ambient pressure, held for 6 h, and then naturally cooled to room temperature to obtain Ta3N5 / Ti x Al y thin film. During this process, flowing ammonia gas was introduced to maintain the ammonia atmosphere in the processing chamber.

[0083] The cocatalyst layer NiFeCoO4 was deposited on the surface of Ta3N5 by electrochemical deposition technology, specifically including: the volume of the electrolyte solution was 200 mL, which was composed of 20 mM Fe(NO3)3·9H2O, 60 mM Ni(NO3)2·6H2O, 40 mM Co(NO3)2·6H2O and deionized water, and stirred at 800 rpm for 30 min to ensure uniform mixing. During the electrodeposition process, continuous stirring at 400 rpm was maintained, and at the same time, a bias of 0.9 V was applied, and the deposition time was 60 s. After this process was completed, the sample needed to be thoroughly rinsed with deionized water.

[0084] Prepare a precursor solution containing 4.5 mL of ultrapure water, 100 μL of 24 mmol / L chloroplatinic acid, 100 μL of 0.2 mol / L potassium carbonate and 100 μL of 1 mol / L ascorbic acid. After reacting for 20 min, 100 μL of 10 mmol / L hydroxylamine hydrochloride was quickly added and shaken until the color was uniform. Take 5 mL of the solution, centrifuge at 11000 rpm for 20 min, discard the supernatant after obtaining the PtNPs colloid. Then add deionized water to 5 mL, centrifuge under the same conditions, discard the supernatant, add absolute ethanol to 5 mL, and ultrasonically treat until dispersed to ensure uniformity. Finally, take 1 mL of the solution and dilute it 50 times with deionized water, and spin-coat 400 μL / cm 2Coated on the surface of the photoanode to obtain PtNPs@NiFeCoO4 / Ta3N5 / Ti x Al y photoelectrode.

[0085] The multilayer film structure of the Ta3N5-based photoelectrode sequentially includes a first Ti metal layer, a Pt conductive metal layer, a Ti x Al y alloy layer, a Ta3N5 layer, and a NiFeCoO4 cocatalyst layer from bottom to top. The thicknesses of each layer are: 30 nm, 200 nm, 100 nm, 700 nm, 10 nm; the average particle size of the MNPs nanometal particles is 20 nm, and it can absorb specific wavelengths in the wavelength range of 590 - 620 nm.

[0086] Comparative Examples 1 - 16

[0087] Refer to the records of the following documents and prepare photoelectrode products respectively.

[0088] Comparative Example 1: Y. Xiao, Z. Fan, M. Nakabayashi, Q. Li, L. Zhou, Q. Wang, C. Li, N. Shibata, K. Domen, Y. Li, Nat. Commun. 2022, 13, 7769.

[0089] Comparative Example 2: G. Liu, S. Ye, P. Yan, F. Xiong, P. Fu, Z. Wang, Z. Chen, J. Shi, C. Li, Energy Environ. Sci. 2016, 9, 1327.

[0090] Comparative Example 3: P. Wang, C. Ding, Y. Deng, H. Chi, H. Zheng, L. Liu, H. Li, Y. Wu, X. Liu, J. Shi, C. Li, ACS Catal. 2023, 13, 2647.

[0091] Comparative Example 4: J. Fu, Z. Fan, M. Nakabayashi, H. Ju, N. Pastukhova, Y. Xiao, C. Feng, N. Shibata, K. Domen, Y. Li, Nat. Commun. 2022, 13, 729.

[0092] Comparative Example 5: B. Zhang, Z. Fa, Y. Chen, C. Feng, S. Li, Y. Li, Angew. Chem. Int. Ed. 2023, 62, e202305123.

[0093] Comparative Example 6: Y. Xiao, C. Feng, J. Fu, F. Wang, C. Li, V. F. Kunzelmann, C. M. Jiang, M. Nakabayashi, N. Shibata, I. D. Sharp, K. Domen, Y. Li, Nat. Catal. 2020, 3, 932.

[0094] Comparative Example 7: Y. He, P. Ma, S. Zhu, M. Liu, Q. Dong, J. Espano, X. Yao, D. Wang, Joule 2017, 1, 831.

[0095] Comparative Example 8: P. Chakthranont, T. R. Hellstern, J. M. McEnaney, T. F. Jaramillo, Adv. Energy Mater. 2017, 7, 1701515.

[0096] Comparative Example 9: S. Guo, Y. Wu, C. Wang, Y. Gao, M. Li, B. Zhang, C. Liu, Nat. Commun. 2022, 13, 5297.

[0097] Comparative Example 10: Z. Shi, J. Feng, H. Shan, X. Wang, Z. Xu, H. Huang, Q. Qian, S. Yan, Z. Zou, Appl. Catal. B - Environ. 2018, 237, 665.

[0098] Comparative Example 11: Y. Pihosh, V. Nandal, T. Minegishi, M. Katayama, T. Yamada, K. Seki, M. Sugiyama, K. Domen, ACS Energy Lett. 2020, 5, 2492.

[0099] Comparative Example 12: Y. Pihosh, T. Minegishi, V. Nandal, T. Higashi, M. Katayama, T. Yamada, Y. Sasaki, K. Seki, Y. Suzuki, M. Nakabayashi, M. Sugiyama, K. Domen, Energy Environ. Sci. 2020, 13, 1519.

[0100] Comparative Example 13: T. Higashi, H. Nishiyama, Y. Suzuki, Y. Sasaki, T. Hisatomi, M. Katayama, T. Minegishi, K. Seki, T. Yamada, K. Domen, Angew. Chem. Int. Ed. 2019, 58, 2300.

[0101] Comparative Example 14: Y. Kawase, T. Higashi, M. Katayama, K. Domen, K. Takanabe, ACS Appl. Mater. Interfaces, 2021, 13, 16317.

[0102] Comparative Example 15: H. R. Kwon, J. W. Yang, S. Choi, W. S. Cheon, I. H. Im, Y. Kim, J. Park, G. H. Lee, H. W. Jang, Adv. Funct. Mater. 2023, 14, 2303342.

[0103] Comparative Example 16: Chinese Patent Application for Invention "Ta3N5-based Photoelectrode Based on Magnetron Sputtering" (CN119040940A).

[0104] Part III Test Results and Data Analysis

[0105] 1. Observation using electron microscopy equipment

[0106] Figure 2 For the MNPs@NiFeCoO z / Ta3N5 / Ti x Al y products prepared in Example 2 of the present invention, HRTEM images at different magnifications can be seen inside the products. Polycrystals and some small holes with a size of several hundred nanometers can be seen, which are the characteristics of the Ta3N5 film formed by replacing oxygen vacancies in the Ta2O5 precursor film with nitrogen vacancies during the nitridation process. A dense multifunctional alloy layer (Ti x Al y ) is formed during the nitridation process. Ti x Al y effectively bonds Ta3N5 to the Pt layer, forming an excellent integrated heterojunction structure. The NiFeCoO z cocatalyst layer is modified to effectively extract photo-generated holes.

[0107] 2. Photocurrent density ratio test

[0108] Refer to the usage method of the aforementioned photoelectrode products to build a test system, and test the products of the examples and each comparative example respectively. Figure 3Comparison of photocurrent density and onset potential between the present invention and existing products in the comparative examples.

[0109] As can be seen from the figure, taking the test result of Example 2 of the present invention as an example, due to the LSPR effect of MNPs, the photocurrent density can reach 12.1 mA cm -2 (marked by pentagrams in the figure); the photocurrent densities in the literatures of Comparative Examples 1-15 are all less than the photocurrent density of 12.1 mA cm -2 (marked by circles in the figure, and the numbers beside the marks refer to the serial numbers of each comparative example). At the same time, the example has the lowest onset potential, which is 0.257 V at 0.2 mA cm -2 RHE .

[0110] Therefore, the MNPs@NiFeCoO prepared by magnetron sputtering method in the present invention z / Ta3N5 / Ti x Al y material can achieve a high photocurrent density, a low onset potential, excellent performance, and exceeds other existing photoanode products.

[0111] 3. Comparative tests of incident monochromatic light-electron conversion efficiency (IPCE), applied bias light-electricity conversion efficiency (ABPE), and onset potential

[0112] Taking the MNPs@NiFeCoO prepared in Example 2 of the present invention z / Ta3N5 / Ti x Al y product and the product prepared in Comparative Example 16 as the test objects, the IPCE, ABPE, and onset potential tests are carried out with reference to the records of the aforementioned comparative example literatures, and the test results are respectively as Figure 4 and Figure 5 shown.

[0113] Due to the LSPR effect of MNPs and the excellent conductivity and relatively high Fermi level of the Ti x Al y alloy layer, the quantum efficiency of the photoanode of Example 2 remains above 80% in the wavelength range of 300-530 nm, which is much higher than that of Comparative Example 16. In addition, the ABPE of the example is increased to 2.81% and has a lower onset potential (0.257 V at 0.2 mA cm -2 RHE ), indicating that the LSPR effect and the special design of the alloy layer play an important role in reducing the recombination rate and accelerating the carrier dynamics.

[0114] ​​Therefore, it can be proved that the technical solution of the present invention is significantly superior to the technical solution of the published document CN119040940A in terms of reducing the recombination rate, accelerating carrier dynamics, and improving quantum efficiency. Such technical effects cannot be achieved by simply adding existing technologies.

[0115] In summary, in the photoanode product of the present invention, Ti x Al y is an alloy layer that acts as a binder to ensure the tight bonding of Ta3N5 with noble metals such as Pt, and is further bonded to the quartz substrate based on the Ti metal layer, which can save the usage of noble metals and expand the application scope. In addition, Ti x Al y alloy layer can, on the one hand, improve the mobility of photoelectrons and induce the separation and migration of EHPs; on the other hand, the Fermi levels of Ti x Al y and Ta3N5 are at -4.13 eV and -4.1 eV respectively, and their energy levels are adapted, which is beneficial to improving the transport of photo-generated carriers. The NiFeCoO z co-catalyst layer modification can effectively extract photo-generated holes. For NiFeCoO z / Ta3N5 / Ti x Al y film layer, metal nanoparticles such as Au, Pt, etc. are loaded to achieve photo-thermal and photo-electric coupling.

[0116] Finally, it should also be noted that the above-listed are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments and there can be many variations. The present invention can be outlined in other specific forms that do not violate the spirit and main features of the present invention. Therefore, in any aspect, the above embodiments of the present invention should only be regarded as an illustration of the present invention and cannot limit the present invention. Any change within the meaning and scope equivalent to the claims of the present invention should be considered to be included within the scope of the claims.

Claims

1. A Ta3N5-based photoelectrode based on vapor deposition technology, characterized in that: The Ta3N5-based photoelectrode is based on quartz glass as a substrate, and has a multilayer film structure formed on the substrate based on magnetron sputtering, electron beam evaporation, thermal nitridation, electrochemical deposition and coating; the multilayer film structure includes, from bottom to top, a first Ti metal layer, a Pt conductive metal layer, a Ti x Al y Alloy layer, Ta3N5 layer, NiFeCoO z Catalyst promoter layer and MNPs nano metal particles; the Ti x Al y The alloy layer is a uniform material layer formed by the reaction of the second Ti metal layer and the Al2O3 layer, and the Ta3N5 layer is a uniform material layer formed by the reaction of the Ta2O5 layer and NH3. z The catalyst promoter layer is a uniform material layer formed by applying gradient bias deposition; the MNPs metal particles contain Au or Pt, and M refers to Au or Pt having photothermal properties.

2. The Ta3N5-based photoelectrode according to claim 1, characterized in that: The thickness of the first Ti metal layer is in the range of 2 to 50 nm, the thickness of the Pt conductive metal layer is in the range of 100 to 200 nm, and the thickness of the Ti x Al y The thickness of the NiFeCoO layer ranges from 20 to 100 nm, the thickness of the Ta3N5 layer ranges from 500 to 700 nm; z The thickness of the catalyst promoter layer is in the range of 2 to 10 nm; the average particle size of the MNPs nano-metal particles is in the range of 5 to 20 nm.

3. The Ta3N5-based photoelectrode according to claim 1, characterized in that: The thickness ratio of the second Ti metal layer to the Al2O3 layer is x / y, and its value range is 1 to 5; the NiFeCoO z The value range of z in the co-catalyst layer is 2-4.

4. The method for preparing a Ta3N5-based photoelectrode based on vapor deposition technology according to claim 1, characterized in that: The following steps are involved: (1) Using a quartz glass plate of appropriate size as a substrate, cleaning it with acetone, anhydrous ethanol, dilute sulfuric acid and deionized water in sequence; (2) firstly, a first Ti metal layer and a Pt conductive metal layer are sequentially deposited on the substrate by a magnetron sputtering process; according to the design scheme of the photoelectrode, the area reserved for conduction is partially shielded, and then a second Ti metal layer and an Al2O3 layer are sequentially deposited by a magnetron sputtering process, and finally a Ta2O5 layer is deposited by an electron beam evaporation process; (3) The sample that has completed the multilayer deposition process is moved into a horizontal quartz tube furnace for thermal nitridation treatment. During this process, the two materials of the second Ti metal layer and the Al2O3 layer react and combine to form a uniform Ti x Al y Alloy layer by layer, the Ta2O5 layer combines with NH3 to transform into a uniform Ta3N5 layer; (4) Electrochemical deposition technology is used to continue to deposit the catalyst layer NiFeCoO on the surface of Ta3N5 z , a gradient bias was applied during the electrodeposition process, and deionized water was used for rinsing after the deposition was completed; (5) Metal nanoparticles (MNPs) were prepared by liquid phase reduction method. The MNPs colloid obtained by the reaction was centrifuged, dispersed, and diluted, and then coated on the Ta3N5 layer on the surface of the sample by spin coating. The sample was further dried at room temperature to obtain a Ta3N5-based photoelectrode with MNPs metal particles on the surface, which was recorded as MNPs@NiFeCoO z / Ta3N5 / Ti x Al y Photoanode.

5. The method according to claim 4, characterized in that During the magnetron sputtering treatment and electron beam evaporation process in step (2), the deposition thickness of each layer on the sample is: the first Ti metal layer is 2 to 50 nm, the Pt metal conductive layer is 100 to 200 nm; the second Ti metal layer is 2 to 50 nm, the Al2O3 layer is 20 to 100 nm, and the Ta2O5 layer is 500 to 700 nm.

6. The method according to claim 4, characterized in that In the step (2), during the magnetron sputtering process, Ar gas is introduced into the magnetron sputtering chamber at a rate of 37 sccm, and the minimum vacuum is maintained at 6.7E. -7 MPa; during the electron beam evaporation process, Ar gas was introduced into the deposition chamber at a rate of 30 sccm to keep the chamber pressure at 1.0E -4 Torr, The deposition rate is deposited.

7. The method according to claim 4, characterized in that During the thermal nitridation treatment in step (3), the sample is heated from room temperature to 950-1000°C at a rate of 5°C / min at normal pressure, kept at this temperature for 6 hours, and then naturally cooled to room temperature; during this process, flowing ammonia gas is introduced to maintain an ammonia atmosphere in the treatment chamber.

8. The method according to claim 4, characterized in that The step (4) specifically comprises: Fe(NO3)3·9H2O, Ni(NO3)2·6H2O and Co(NO3)2·6H2O were taken in a molar ratio of 1:3:2, added to an appropriate amount of deionized water, mixed evenly and prepared into an electrolyte solution for electrochemical deposition; the sample after thermal nitridation was immersed in the electrolyte solution as the working electrode, and a calomel electrode was used as the reference electrode and a platinum sheet was used as the counter electrode, and the electrochemical deposition process was carried out using a three-electrode system; during the electrochemical deposition process, continuous stirring at 400 rpm was maintained, and a gradient bias of 0.65 to 0.9 V was applied at the same time, and the deposition time was 60 s.

9. The method according to claim 4, characterized in that In the step (5), Au or Pt chloride complex acid is fully shaken to obtain MNPs precursor solution, further reacted with potassium carbonate and ascorbic acid, and then hydroxylamine hydrochloride is added and shaken until the color is uniform; deionized water is added to the reaction product for centrifugal treatment to obtain MNPs colloid; anhydrous ethanol is added for ultrasonic dispersion, and the dispersed suspension is diluted at a ratio of 1:50 for spin coating operation, and the coating amount is 100 to 400 μL / cm 2 .

10. The method according to claim 4, characterized in that In the step (5), by controlling the reaction time, cleaning operation and coating thickness of the MNPs precursor solution, the particle size of the MNPs nanometal particles on the surface of the Ta3N5-based photoelectrode is 5 to 20 nm and can absorb a specific wavelength in the wavelength range of 500 to 620 nm.

Citation Information

Patent Citations

  • Method for preparing hydrocarbon through photoelectric-photo-thermal coupling with water and CO2 as raw materials

    CN116770331A

  • Ta3N5-based photoelectrode based on magnetron sputtering and preparation method

    CN119040940A

Cited By

  • Specialized vehicle system comprising a hyperbaric oxygen chamber

    KR102976249B1